Does Performing Drop Jumps With Additional Eccentric Loading Improve Jump Performance? - Aboodarda, S.J.; Byrne, J.M.; Samson, M.; Wilson, B.D.; Mokhtar, A.H.; Behm, D.G. (Lippincott, Williams & Wilkins, 2014)
Does performing drop jumps with additional eccentric loading improve jump performance? J Strength Cond Res 28(8): 2314–2323, 2014—Previous investigators have speculated that applying additional external load throughout the eccentric phase of the jumping movement could amplify the stretch-shortening cycle mechanism and modulate jumping performance and jump exercise intensity. The aims of this study, therefore, were to determine the effect of increased eccentric phase loading, as delivered using an elastic device, on drop jumps (DJs) performed from different drop heights. Of specific interest were changes in (a) the kinetics; eccentric and concentric impulse, rate of force development (RFD), concentric velocity and (b) the electromyographic (EMG) activity of leg muscles. In a randomized repeated-measure study, 15 highly resistance trained male subjects performed DJs from 3 heights (20, 35, and 50 cm) under 3 different conditions: body weight only (free DJ) and with elastic bands providing downward force equivalent to 20% (+20% DJ) and 30% (+30% DJ) of body mass. All DJs were recorded using video and force plate data that were synchronized with EMG data. Results demonstrated that using additional tensile load during the airborne and eccentric phases of the DJ could enhance eccentric impulse (p = 0.042) and RFD (p < 0.001) and resulted in small to moderate effect size (ES) increases in quadriceps intergrated EMG across the eccentric phase (0.23 > ES > 0.51). The observed greater eccentric loading, however, did not immediately alter concentric kinetics and jump height nor did it alter muscle activation levels during this phase. The findings indicated that, in addition to the conventional technique of increasing drop height, using a tensile load during the airborne and eccentric phases of the DJ could further improve eccentric loading of DJs. As it has been suggested that eccentric impulse and RFD are indicators of DJ exercise intensity, these findings suggest that the loaded DJs, using additional elastic load, may be an effective technique for improving DJ exercise intensity without acute effects on the jumping performance and neuromuscular activation level in highly trained athletes.